2004
DOI: 10.1074/jbc.m405071200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cδ Activation Induces Apoptosis in Response to Cardiac Ischemia and Reperfusion Damage

Abstract: Heart attacks caused by occlusion of coronary arteries are often treated by mechanical or enzymatic removal of the occlusion and reperfusion of the ischemic heart. It is now recognized that reperfusion per se contributes to myocardial damage, and there is a great interest in identifying the molecular basis of this damage. We recently showed that inhibiting protein kinase C␦ (PKC␦) protects the heart from ischemia and reperfusion-induced damage. Here, we demonstrate that PKC␦ activity and mitochondrial transloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
148
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(176 citation statements)
references
References 66 publications
18
148
2
1
Order By: Relevance
“…δPKC levels were normalized using calnexin, an ER resident chaperone protein. Since δPKC is known to translocate to mitochondria [13,15], we confirmed that mitochondria are not present in this ER fraction using Western blotting against the mitochondrial protein, adenine nucleotide translocase (ANT) [17] (Fig. 3A; ANT is detected in the mitochondrial fraction, though Fig.…”
Section: δPkc Translocates To the Endoplasmic Reticulum Following Tunmentioning
confidence: 67%
See 4 more Smart Citations
“…δPKC levels were normalized using calnexin, an ER resident chaperone protein. Since δPKC is known to translocate to mitochondria [13,15], we confirmed that mitochondria are not present in this ER fraction using Western blotting against the mitochondrial protein, adenine nucleotide translocase (ANT) [17] (Fig. 3A; ANT is detected in the mitochondrial fraction, though Fig.…”
Section: δPkc Translocates To the Endoplasmic Reticulum Following Tunmentioning
confidence: 67%
“…Using dominant negative mutants of δPKC, broad spectrum inhibitors or a specific δPKC antagonist peptide, δPKC was further demonstrated to be a mediator of apoptosis [13,18,37,38]. Few studies have reported an antiapoptotic role for δPKC [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations